MSc in crop protection - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Three major UK research centres are collaborating to offer a new one-year post graduate course for UK and overseas students. The aim of the course is to give students a thorough understanding of the principles and practice of modern crop...